Model Problem Based Learning Berbantuan Socio-Scientific Issues terhadap Keterampilan Berpikir Kritis: Kajian Literatur - Oktariana, Rini; Arsih, Fitri (TSAQOFAH, 2026)
Critical thinking skills are an essential competence that must be developed from the school years; however, synthesis studies that specifically examine the effectiveness of the Problem Based Learning (PBL) model supported by Socio-Scientific Issues (SSI) in developing these skills remain limited. This study aimed to examine the influence of PBL supported by SSI on students’ critical thinking skills through a literature review of 10 relevant articles obtained from Google Scholar using the keywords critical thinking, Problem Based Learning, and Socio-Scientific Issues. The method employed was a literature review by identifying, selecting, and analyzing research findings related to the implementation of PBL supported by SSI in the context of science learning. The review results indicate that PBL supported by SSI consistently contributes to improving students’ critical thinking skills, particularly in the aspects of analysis, evaluation, and decision-making. These findings strengthen the theoretical and empirical foundation for implementing PBL supported by SSI as an effective science learning strategy to develop students’ critical thinking skills.